A study on the mechanism and usefulness of the floater shot in basketball - Machida, Y.; Uchiyama, H.; Yoshida, K.; Ikeda, E.; Hashizume, J.; Kashiwakura, H. (Japan Journal of Physical Education, Health and Sport Sciences, 2016)
Low scoring within the paint area is the biggest issue for the Japan men's national basketball team, and therefore it is necessary for them to acquire a new approach to shooting that would increase the attacking variations for attempting a higher percentage of shots within this area. This study focused on the validity of the floater shot as a new offensive approach for overcoming this problem, and examined its usefulness and mechanism using three-dimensional motion analysis (VICONMX+). Comparison of the floater shot with the jump shot and lay-up shot revealed that the mechanism of the former involved (1) absence of a shooting posture, (2) a low vertical jump involving a slow step, (3) raising the shooting arm in a vertical direction, and (4) a highly arched ball trajectory with a height roughly the same as that of the top of the backboard. Our examination also revealed that maintaining one's distance from the defense through a weak jump and retroversion of the trunk, upsetting the timing of the blocking shot through release from a non-stopping motion, and shooting the ball over the hand during the blocking shot through the high-arched ball trajectory by elevating the shooting arm in a vertical direction were useful for achieving a high percentage of shots within the paint area, where the influences of height and selective defense are greater. These results are of relevance to not only the Japan men's national basketball team but also any team with a smaller stature when considering how to improve the scoring rate within the paint area.